2020
DOI: 10.1186/s12913-020-05258-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of community pharmacists in weight management: results of a national study in Lebanon

Abstract: Background Ideally situated within the community, pharmacists can be involved in a broad range of health promotion campaigns including prevention of obesity. Limited evidence is available regarding their involvement in weight management in Lebanon, a country with escalating prevalence rate of obesity. Objective To examine the role of community pharmacists in weight management in Lebanon, specifically studying their beliefs, current practices, servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 46 publications
4
20
0
1
Order By: Relevance
“…On one hand, the majority of participants reported receiving good education of the CAM product, its side effects and mode of use. Such results are in accordance with a previous investigation about the services of weight management among community pharmacists in Lebanon, and which showed a broad range of services that the pharmacists offered to assist their patients in controlling their weight [ 24 ]. Together, these findings further underscore the fact that the pharmacist’s involvement in CAM products is in fact an extension of their roles in pharmaceutical care, clinical pharmacy practices and collaborative healthcare teams’.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…On one hand, the majority of participants reported receiving good education of the CAM product, its side effects and mode of use. Such results are in accordance with a previous investigation about the services of weight management among community pharmacists in Lebanon, and which showed a broad range of services that the pharmacists offered to assist their patients in controlling their weight [ 24 ]. Together, these findings further underscore the fact that the pharmacist’s involvement in CAM products is in fact an extension of their roles in pharmaceutical care, clinical pharmacy practices and collaborative healthcare teams’.…”
Section: Discussionsupporting
confidence: 92%
“…Together, these findings further underscore the fact that the pharmacist’s involvement in CAM products is in fact an extension of their roles in pharmaceutical care, clinical pharmacy practices and collaborative healthcare teams’. Professional associations, such as the American College of Clinical Pharmacy (ACCP), the American Society of Health-System Pharmacists and the Canadian Society of Hospital Pharmacists, have recommended that the profession of pharmacy actively embrace dietary supplements (natural health products, vitamins and minerals) as part of the pharmacist’s scope of practice [ 24 , 45 ]. On the other hand, however, a significant proportion of interviewed CAM users reported that pharmacists were not asking question about their medical history before dispensing CAM products nor were they providing information on CAM-drug interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding concurs with the result of other study which reported that CPPs believed metabolic syndrome as a common health problem in the country that is largely related to obesity and sedentary lifestyles of the public [ 25 ]. Another study completed from Lebanon also noted that more than 80% of CPPs agreed as they have a pivotal role in weight reduction efforts [ 14 ]. A high percentage of participants disagreed (41.5%) and remained neutral (36.9%) to statement that mentions as the public awareness towards the link between metabolic syndrome and the high risk for cardiovascular diseases and type 2 diabetes is poor.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study reported that pharmacist-physician collaborative practice in the care of patients with the MetS increased the proportion of patients who has get rid of the syndrome after yielding a significant improvement in blood pressure control and triglycerides levels over a 6 month period [ 13 ]. Another study completed in Lebanon stated that more than 80% of CPPs agreed that they have a key role to play in weight reduction [ 14 ].…”
Section: Introductionmentioning
confidence: 99%